Comparison of O-RADS with the ADNEX model and IOTA SR for risk stratification of adnexal lesions: a systematic review and meta-analysis - Han, Jing; Wen, Jing; Hu, Wei (Frontiers in Oncology, 2024)
Purpose: This study aims to systematically compare the diagnostic performance of the Ovarian-Adnexal Reporting and Data System with International Ovarian Tumor Analysis group Simple Rules and the Assessment of Different Neoplasias in the adnexa model for risk stratification of ovarian cancer and adnexal masses. Methods: A literature search of online databases for relevant studies up to July 2023 was conducted by two independent reviewers. The summary estimates were pooled with the hierarchical summary receiver-operating characteristic model. The quality of the included studies was assessed with the Quality Assessment of Diagnostic Accuracy Studies-2 and the Quality Assessment of Diagnostic Accuracy Studies-Comparative tool. Meta-regression and subgroup analyses were performed to explore the impact of varying clinical settings. Results: A total of 13 studies met the inclusion criteria. The pooled sensitivity and specificity for 8 head-to-head studies between Ovarian-Adnexal Reporting and Data System and the Assessment of Different Neoplasias in the adnexa model were 0.96 (95% CI 0.92-0.98) and 0.82 (95% CI 0.71-0.90) vs. 0.94 (95% CI 0.91-0.95) and 0.83 (95% CI 0.77-0.88); and for 7 head-to-head studies between Ovarian-Adnexal Reporting and Data System and the International Ovarian Tumor Analysis group Simple Rules were 0.95 (95% CI 0.93-0.97) and 0.75 (95% CI 0.62-0.85) vs. 0.91 (95% CI 0.82-0.96) and 0.86 (95% CI 0.76-0.93). No significant differences were found between Ovarian-Adnexal Reporting and Data System and the Assessment of Different Neoplasias in the adnexa model as well as the International Ovarian Tumor Analysis group Simple Rules in terms of sensitivity (P=0.57 and P=0.21) and specificity (P=0.87 and P=0.12). Substantial heterogeneity was observed among studies for all 3 guidelines. Conclusions: All three guidelines demonstrated high diagnostic performance, and no significant differences were observed between the 3 guidelines either for sensitivity or for specificity.